Epidemiology of injuries at the first transplant football world cup - Totti, Valentina; Ferrari, Filippo; Paltrinieri, Simone; Vitale, Giovanni; Mosconi, Giovanni; Nanni Costa, Alessandro; Sella, Gianluigi; Morelli, Maria Cristina; Caraceni, Paolo; Roi, Giulio Sergio (Frontiers in Sports and Active Living, 2025)
IntroductionRecreational football is widely recognized as a health-promoting activity, with proven long-term benefits for physical and mental well-being. For transplant recipients, it offers additional value by supporting recovery, reintegration, and quality of life. To promote safe participation in sport among this population, the World Transplant Games Federation launched the 1st World Transplant Football Cup. This study aimed to investigate the epidemiology of injuries sustained during the tournament.MethodsMatches were conducted according to modified FIFA 7-a-side rules, tailored to ensure the safety of transplanted organs and tissues. Each team included up to 16 players of any age or gender. Matches lasted 20 min, with unlimited substitutions. Games were played on two standard 60 × 40 m pitches with 3 m goals. Medical coverage was ensured by two sports physicians present throughout the event. Injury data were collected using a standardized form for all requests for medical intervention (RfMI).ResultsA total of 172 transplant recipients participated (kidney: n = 103; liver: n = 25; bone marrow: n = 18; heart: n = 14; kidney-pancreas: n = 7; lung: n = 5), representing 11 teams. Across 35 matches (total exposure: 326 h and 40 min), 28 RfMIs were reported (16% of participants). Players (mean age 36.0 ± 11.1 years) included 26 males and 2 females, distributed across all field positions. Injury mechanisms were non-contact (43%), indirect contact (32%), and direct contact (25%). Most injuries were acute (82%), followed by acute-on-chronic (12%) and chronic (4%). The most frequent injury types were contusions (32%), sprains (21%), muscle strains (18%), and abrasions (14%), with less common events including tendinopathies, minor concussions, and toe infections (4%). The incidence of RfMI was 85.7 per 1,000 h (95% CI: 54.0–117.4), and time-loss injuries (n = 17) occurred at a rate of 52.0 per 1,000 h (95% CI: 27.3–76.8). All injuries were managed on site, except one which required hospital care.ConclusionsDespite a moderate incidence of injury, the majority were minor and no transplant-related injuries were recorded. These findings support the safety and feasibility of recreational football in transplant recipients, reinforcing its role as a beneficial component of long-term health promotion.